2014
DOI: 10.1007/s13202-014-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy modeling of volume reduction of oil due to dissolved gas runoff and pressure release

Abstract: Oil formation volume factor (FVF) refers to the change in oil volume between reservoir and standard conditions at surface. It is a crucial oil property which is governed by reservoir temperature, amount of dissolved gas in oil, and specific gravity of oil and dissolved gas. This parameter plays a trivial role in petroleum reservoir and production calculations. Accurate determination of oil FVF is restricted by limitations on reliable sampling and high cost and time-consumption associated with laboratory experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To achieve an optimal fuzzy model, different clustering radii were introduced to subtract clustering algorithm and the performance of the consequent fuzzy model was investigated. Subtractive clustering was generated by a design parameter, called clustering radii (Zargar et al , 2014). Each cluster may contain a variety of mass composition of cementitious materials.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve an optimal fuzzy model, different clustering radii were introduced to subtract clustering algorithm and the performance of the consequent fuzzy model was investigated. Subtractive clustering was generated by a design parameter, called clustering radii (Zargar et al , 2014). Each cluster may contain a variety of mass composition of cementitious materials.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 provides an opportunity to compare MSE and R-square factors of different models. Results show that committee machine surpasses other methods and provides more reliable results relative to Zargar et al (2014), , and individual SVR and ACE models.…”
Section: Committee Machine With Ace and Svrmentioning
confidence: 96%
“…Graph evaluating the performance of committee machine model using concepts of correlation coefficient, relative error, and residual analysis of prediction. Zargar et al (2014) proposed a fuzzy logic model for estimating FVF from available PVT data. Performing an error distribution analysis, they concluded that the fuzzy model is an accurate model for FVF estimation.…”
Section: Committee Machine With Ace and Svrmentioning
confidence: 99%
See 1 more Smart Citation